The effect of work overload and role conflict on job stress among government teachers at Kota Bharu, Kelantan - Nurul Atikah, Mohd Nor Hakimin (2023)
Education plays a pivotal role in a nation's development, and the quality of education is closely tied to the effectiveness of the educational system. Enhancing educational standards through system modernization and emphasizing teacher quality is the goal of the Plan Pembangunan Pendidikan Malaysia (PPPM) 2013–2025. A growing number of teachers have expressed their intention to leave their jobs due to stress at work, highlighting the difficulties facing the teaching profession. According to the objectives of the PPPM, this study explores the connection between role conflict, work overload, and job stress among government school teachers in Kota Bharu, Kelantan. With a focus on role conflict and work overload as well as the degree of workplace stress, three research questions direct the study. The study uses a sample of 328 instructors from government schools and a quantitative methodology based on surveys. The findings show that teachers experience high levels of occupational stress, with role conflict and work overload being major contributors to this stress. The results provide insightful information for administrators, legislators, and teacher unions by highlighting the necessity of actions to control workload and define roles. Despite limitations, the present study furnishes important evidence, hence clearing the path for subsequent investigations to augment our comprehension and formulate all-encompassing approaches to tackle job stress in educators, guaranteeing their welfare and the level of education they impart.